Pengujian Sistem Rekomendasi Penilaian Pengemudi Transportasi Umum Nasional Menggunakan Path Testing pada White Box Testing - Safrizal, Safrizal (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2025)
Driver assessment recommendation system to conduct assessment and recommendations of national public transportation driver competency and behavior. To ensure the reliability and stability of the program logic in this system, testing is carried out using the White Box Testing approach, especially the Path Testing method. This method tests each execution path in the program control structure to identify potential logic errors and ensure that each condition has been thoroughly tested. Testing is carried out by calculating cyclomatic complexity, describing the program flowchart, and identifying and tracing independent paths. The test results show that all logic paths have run as expected without any functional defects. This indicates that the system has a strong logic structure and is ready to be integrated into a national-scale operational environment. Thus, Path Testing has proven effective in ensuring system quality in terms of internal structure.